2017
DOI: 10.1016/j.ijid.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tuberculous lymphadenitis in slaughtered cattle in Eastern Cape, South Africa

Abstract: The presence of live Mycobacterium strains in slaughtered cattle poses a health risk to beef consumers and abattoir workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…These techniques amplify two or more target genes in a reaction simultaneously [ 114 , 115 ]. A single target could end in a false-negative result, as a number of the targeted genes are not present in some MTBC strains [ 115 , 116 ]. The most efficient approach is one based on primers that amplify segments of the IS6110 element, especially targeting the 123 bp and 245 bp fragments.…”
Section: Molecular Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques amplify two or more target genes in a reaction simultaneously [ 114 , 115 ]. A single target could end in a false-negative result, as a number of the targeted genes are not present in some MTBC strains [ 115 , 116 ]. The most efficient approach is one based on primers that amplify segments of the IS6110 element, especially targeting the 123 bp and 245 bp fragments.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Another PCR that produces excellent recognition of M. bovis isolates relies on the amplification of a 500 bp DNA segment, especially targeted for the 123 bp and 245 bp fragments inside the RvD 1Rv2031c genomic sequence [ 118 , 119 ]. Multiplex PCR has the advantage of being fast and accurate and can differentiate M. bovis from other members of MTBC by amplification of two DNA fragments [ 115 , 116 , 120 ].…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Most farmers (nearly 70%) in South Africa live in harsh agroecological zones unbefitting for producing crops, which necessitates them to focus on livestock agriculture to make a livelihood. In South Africa, the Eastern Cape Province has one of the highest numbers of cattle, and its economy is dependent on livestock farming, which plays an important role in the nation's economy [23]. This project was approved by the University of Fort Hare Research Ethics Committee (UREC), and an ethical clearance certificate, REC-270710-028-RA, was issued.…”
Section: Study Setting and Ethical Considerationmentioning
confidence: 99%
“…Yet again, in 2014 Bhembe et al [20] reported 5% prevalence of MTBC with 100% MDR-TB from TB patients. In 2017, Bhembe et al [23] investigated the prevalence of resistant MDR-TB in cattle farmers. The study reported 156 cases of MDR-TB in the province.…”
Section: Introductionmentioning
confidence: 99%
“…El diagnóstico de la tuberculosis bovina se puede lograr mediante el uso de métodos de laboratorio convencionales como cultivo y frotis al microscopio, Estos métodos son económicos pero su sensibilidad es baja, recientemente, técnicas moleculares de mejor rendimiento y más asequibles han sido introducidas como PCR, el método de diagnóstico más utilizado para la detección de animales tuberculosos es la prueba de tuberculina, que puede realizarse de tres formas: por la prueba simple cervical, cervical comparativa o del pliegue caudal, otras pruebas diagnósticas utilizadas son el ensayo de interferóngamma(IFN-γ) y pruebas ELISA para detección de anticuerpos. (BHEMBE et al, 2017;OLIVEIRA et al, 2007;CASAL et al, 2017) El objetivo de este estudio fue describir y d o c u m e n t a r l a s c a r a c t e r í s t i c a s anatomopatologicas de un bovino infectado con tuberculosis en Viçosa, MG, Brasil.…”
Section: Introduccionunclassified